Dynamik und Kommunikation prähistorischer Gesellschaften im zentralen Alpenraum Konzepte zu Mobilität und Netzwerken - Brunner, Mirco (Open Series in Prehistoric Archaeology, 2023)
In southern Central Europe, the Alps represent both barriers and communication spaces. Across these topographical, natural boundaries, archaeological find situations repeatedly provide numerous evidences of transalpine mobility, whose development in the course of prehistoric epochs is recognisable in various forms of interactions and networks. The accompanying visible transformation processes in the archaeological find material can be considered under the question of socio-cultural and socio-economic connections between settlement communities. The focus of the study area is on the Alpine Rhine Valley and the neighbouring inner Alpine valley landscapes as well as the regions at the exit of the traverse with their high density of prehistoric settlement sites. The aim of this study is a diachronic synthesis from the Neolithic to the Bronze Age in order to develop models of mobility and networks on the basis of selected sites in the central Alpine region, which are characterised by the diversity of the ceramic find material and its stylistic changes.